Pengaruh Pertumbuhan Penduduk, Tingkat Partisipasi Angkatan Kerja, dan Rasio Beban Ketergantungan Terhadap Pertumbuhan Ekonomi Provinsi Jambi - Edwin Maulana Rozmar; Junaidi Junaidi; Adi Bhakti (Konsentrasi Ekonomi Sumberdaya Alam dan Manusia, Prodi Ekonomi Pembangunan, Fakultas Ekonomi dan Bisnis, Universitas Jambi, 2017)
This research is called population growth, labor force participation rate, and dependency ratio to economic growth of Jambi Province. The purpose of this study was to analyze population growth, labor force participation rate, and load ratio to economic growth of Jambi Province. Analytical methods used are qualitative analysis and quantitative analysis. By using data analysis regression data processing tool is done by using Microsoft Excel and Eviews Software program. In addition, the results indicate that the independent variables have a significant influence on economic growth, while in most indicates that population growth is very significant to economic growth, while the LFPR and dependency ratio is not significant to the economic growth of the district and city in Jambi Province.